2018
DOI: 10.1016/j.memsci.2018.03.077
|View full text |Cite
|
Sign up to set email alerts
|

Assembly of 2D MXene nanosheets and TiO2 nanoparticles for fabricating mesoporous TiO2-MXene membranes

Abstract: A simple and scalable method was proposed for the preparation of the mesoporous membranes by assembling 2D MXene nanosheets and TiO2 nanoparticles (NPs) on a macroporous support. MXene nanosheets were introduced into TiO2 hydrosol, and then transformed the gel for fabrication of mesoporous TiO2@MXene membranes. Characterization results confirmed that an assembled structure of TiO2@MXene nanosheets was formed, benefiting from the nanosheets as 'floor tiles', thereby successfully inhibiting the sol infiltration … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 61 publications
(21 citation statements)
references
References 40 publications
0
17
0
Order By: Relevance
“…Likewise, dip coating of MXene materials on a four-channel ceramic α-Al 2 O 3 hollow fiber support was also demonstrated. [92] Another key parameter in NLM fabrication lies in the solution processability of MXene-based materials, which is also linked to the rheological properties of dispersions. It has been shown that the colloidal dispersions of Ti 3 C 2 T x may exhibit viscoelastic behaviors at different concentrations depending on the rate of exfoliation.…”
Section: Nanolaminate Membranesmentioning
confidence: 99%
See 2 more Smart Citations
“…Likewise, dip coating of MXene materials on a four-channel ceramic α-Al 2 O 3 hollow fiber support was also demonstrated. [92] Another key parameter in NLM fabrication lies in the solution processability of MXene-based materials, which is also linked to the rheological properties of dispersions. It has been shown that the colloidal dispersions of Ti 3 C 2 T x may exhibit viscoelastic behaviors at different concentrations depending on the rate of exfoliation.…”
Section: Nanolaminate Membranesmentioning
confidence: 99%
“…In another interesting work, researchers have prepared MXene-incorporated mesoporous TiO 2 membranes and tested them for dextran rejection (Figure 5h). [92] Importantly, they used 1.0 wt% MXene nanosheets only. They coated disc-shaped and hollow fiber α-Al 2 O 3 supports with MXene dispersion by spin coating and dip coating, respectively.…”
Section: Wastewater Treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…[171,172] For instance, Xu et al prepared MXene-based membranes via spin coating on polyacrylonitrile (PAN). [173] A dip-coating method was also reported for the preparation of MXene membranes on a ceramic α-Al 2 O 3 substrate. [173] Rheological characteristics of the MXene colloidal dispersion play a key role in synthesizing such membranes.…”
Section: Nanolaminate Membranesmentioning
confidence: 99%
“…[112,[181][182][183][184][185][186][187][188][189][190][191][192] These appealing properties have created a lot of interest in the use of MXenes in many fields including membrane separation. [112,163,173,181,185,187,189,190,[193][194][195][196] Most of MXene-based membranes used for water purification have been benefitted from MXenes' 2D multilayers structure, especially the interlayer spacing and the nanosheets orientation. [112,173,181,187,190,196] Selfstanding and supported membranes have been fabricated from Ti 3 C 2 T x MXene.…”
Section: Ion Separation Of Mxene-based Membranesmentioning
confidence: 99%